Reimagining the Grimms’ Fairy Tales: New and Familiar Perspectives in Austrian Picturebook Illustration - Marlene Zöhrer (Strenae)
Three case studies on the illustrations of Lisbeth Zwerger, Linda Wolfsgruber and Renate Habinger – as well as Michael Roher – show to what extent Austrian fairy tale illustration rediscovers the old and established, finds the familiar in the new and yet breaks with the iconographic tradition.